MAYBE Initial complexity problem: 1: T: (1, 1) f0(a, b, c, d, e) -> f9(f, f, f, 0, e) (?, 1) f9(a, b, c, d, e) -> f9(a, b, c, d + 1, f) [ c >= d + 1 ] (?, 1) f24(a, b, c, d, e) -> f24(a, b, c, d, e) [ 0 >= f + 1 ] (?, 1) f24(a, b, c, d, e) -> f24(a, b, c, d, e) (?, 1) f37(a, b, c, d, e) -> f37(a, b, c, d, e) [ f >= g + 1 ] (?, 1) f37(a, b, c, d, e) -> f37(a, b, c, d, e) (?, 1) f37(a, b, c, d, e) -> f48(a, b, c, d, e) (?, 1) f24(a, b, c, d, e) -> f37(a, b, c, d, e) (?, 1) f9(a, b, c, d, e) -> f24(a, b, c, d, e) [ d >= c ] start location: f0 leaf cost: 0 Slicing away variables that do not contribute to conditions from problem 1 leaves variables [c, d]. We thus obtain the following problem: 2: T: (?, 1) f9(c, d) -> f24(c, d) [ d >= c ] (?, 1) f24(c, d) -> f37(c, d) (?, 1) f37(c, d) -> f48(c, d) (?, 1) f37(c, d) -> f37(c, d) (?, 1) f37(c, d) -> f37(c, d) [ f >= g + 1 ] (?, 1) f24(c, d) -> f24(c, d) (?, 1) f24(c, d) -> f24(c, d) [ 0 >= f + 1 ] (?, 1) f9(c, d) -> f9(c, d + 1) [ c >= d + 1 ] (1, 1) f0(c, d) -> f9(f, 0) start location: f0 leaf cost: 0 Repeatedly removing leaves of the complexity graph in problem 2 produces the following problem: 3: T: (?, 1) f9(c, d) -> f24(c, d) [ d >= c ] (?, 1) f24(c, d) -> f37(c, d) (?, 1) f37(c, d) -> f37(c, d) (?, 1) f37(c, d) -> f37(c, d) [ f >= g + 1 ] (?, 1) f24(c, d) -> f24(c, d) (?, 1) f24(c, d) -> f24(c, d) [ 0 >= f + 1 ] (?, 1) f9(c, d) -> f9(c, d + 1) [ c >= d + 1 ] (1, 1) f0(c, d) -> f9(f, 0) start location: f0 leaf cost: 1 A polynomial rank function with Pol(f9) = 2 Pol(f24) = 1 Pol(f37) = -1 Pol(f0) = 2 orients all transitions weakly and the transitions f9(c, d) -> f24(c, d) [ d >= c ] f24(c, d) -> f37(c, d) strictly and produces the following problem: 4: T: (2, 1) f9(c, d) -> f24(c, d) [ d >= c ] (2, 1) f24(c, d) -> f37(c, d) (?, 1) f37(c, d) -> f37(c, d) (?, 1) f37(c, d) -> f37(c, d) [ f >= g + 1 ] (?, 1) f24(c, d) -> f24(c, d) (?, 1) f24(c, d) -> f24(c, d) [ 0 >= f + 1 ] (?, 1) f9(c, d) -> f9(c, d + 1) [ c >= d + 1 ] (1, 1) f0(c, d) -> f9(f, 0) start location: f0 leaf cost: 1 Applied AI with 'oct' on problem 4 to obtain the following invariants: For symbol f24: X_2 >= 0 /\ -X_1 + X_2 >= 0 For symbol f37: X_2 >= 0 /\ -X_1 + X_2 >= 0 For symbol f9: X_2 >= 0 This yielded the following problem: 5: T: (1, 1) f0(c, d) -> f9(f, 0) (?, 1) f9(c, d) -> f9(c, d + 1) [ d >= 0 /\ c >= d + 1 ] (?, 1) f24(c, d) -> f24(c, d) [ d >= 0 /\ -c + d >= 0 /\ 0 >= f + 1 ] (?, 1) f24(c, d) -> f24(c, d) [ d >= 0 /\ -c + d >= 0 ] (?, 1) f37(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 /\ f >= g + 1 ] (?, 1) f37(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 ] (2, 1) f24(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 ] (2, 1) f9(c, d) -> f24(c, d) [ d >= 0 /\ d >= c ] start location: f0 leaf cost: 1 By chaining the transition f0(c, d) -> f9(f, 0) with all transitions in problem 5, the following new transitions are obtained: f0(c, d) -> f24(f, 0) [ 0 >= 0 /\ 0 >= f ] f0(c, d) -> f9(f, 1) [ 0 >= 0 /\ f >= 1 ] We thus obtain the following problem: 6: T: (1, 2) f0(c, d) -> f24(f, 0) [ 0 >= 0 /\ 0 >= f ] (1, 2) f0(c, d) -> f9(f, 1) [ 0 >= 0 /\ f >= 1 ] (?, 1) f9(c, d) -> f9(c, d + 1) [ d >= 0 /\ c >= d + 1 ] (?, 1) f24(c, d) -> f24(c, d) [ d >= 0 /\ -c + d >= 0 /\ 0 >= f + 1 ] (?, 1) f24(c, d) -> f24(c, d) [ d >= 0 /\ -c + d >= 0 ] (?, 1) f37(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 /\ f >= g + 1 ] (?, 1) f37(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 ] (2, 1) f24(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 ] (2, 1) f9(c, d) -> f24(c, d) [ d >= 0 /\ d >= c ] start location: f0 leaf cost: 1 By chaining the transition f0(c, d) -> f9(f, 1) [ 0 >= 0 /\ f >= 1 ] with all transitions in problem 6, the following new transitions are obtained: f0(c, d) -> f24(f, 1) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ 1 >= f ] f0(c, d) -> f9(f, 2) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 ] We thus obtain the following problem: 7: T: (1, 3) f0(c, d) -> f24(f, 1) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ 1 >= f ] (1, 3) f0(c, d) -> f9(f, 2) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 ] (1, 2) f0(c, d) -> f24(f, 0) [ 0 >= 0 /\ 0 >= f ] (?, 1) f9(c, d) -> f9(c, d + 1) [ d >= 0 /\ c >= d + 1 ] (?, 1) f24(c, d) -> f24(c, d) [ d >= 0 /\ -c + d >= 0 /\ 0 >= f + 1 ] (?, 1) f24(c, d) -> f24(c, d) [ d >= 0 /\ -c + d >= 0 ] (?, 1) f37(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 /\ f >= g + 1 ] (?, 1) f37(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 ] (2, 1) f24(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 ] (2, 1) f9(c, d) -> f24(c, d) [ d >= 0 /\ d >= c ] start location: f0 leaf cost: 1 By chaining the transition f0(c, d) -> f9(f, 2) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 ] with all transitions in problem 7, the following new transitions are obtained: f0(c, d) -> f24(f, 2) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ 2 >= f ] f0(c, d) -> f9(f, 3) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 ] We thus obtain the following problem: 8: T: (1, 4) f0(c, d) -> f24(f, 2) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ 2 >= f ] (1, 4) f0(c, d) -> f9(f, 3) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 ] (1, 3) f0(c, d) -> f24(f, 1) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ 1 >= f ] (1, 2) f0(c, d) -> f24(f, 0) [ 0 >= 0 /\ 0 >= f ] (?, 1) f9(c, d) -> f9(c, d + 1) [ d >= 0 /\ c >= d + 1 ] (?, 1) f24(c, d) -> f24(c, d) [ d >= 0 /\ -c + d >= 0 /\ 0 >= f + 1 ] (?, 1) f24(c, d) -> f24(c, d) [ d >= 0 /\ -c + d >= 0 ] (?, 1) f37(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 /\ f >= g + 1 ] (?, 1) f37(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 ] (2, 1) f24(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 ] (2, 1) f9(c, d) -> f24(c, d) [ d >= 0 /\ d >= c ] start location: f0 leaf cost: 1 By chaining the transition f0(c, d) -> f9(f, 3) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 ] with all transitions in problem 8, the following new transitions are obtained: f0(c, d) -> f24(f, 3) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ 3 >= f ] f0(c, d) -> f9(f, 4) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 ] We thus obtain the following problem: 9: T: (1, 5) f0(c, d) -> f24(f, 3) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ 3 >= f ] (1, 5) f0(c, d) -> f9(f, 4) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 ] (1, 4) f0(c, d) -> f24(f, 2) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ 2 >= f ] (1, 3) f0(c, d) -> f24(f, 1) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ 1 >= f ] (1, 2) f0(c, d) -> f24(f, 0) [ 0 >= 0 /\ 0 >= f ] (?, 1) f9(c, d) -> f9(c, d + 1) [ d >= 0 /\ c >= d + 1 ] (?, 1) f24(c, d) -> f24(c, d) [ d >= 0 /\ -c + d >= 0 /\ 0 >= f + 1 ] (?, 1) f24(c, d) -> f24(c, d) [ d >= 0 /\ -c + d >= 0 ] (?, 1) f37(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 /\ f >= g + 1 ] (?, 1) f37(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 ] (2, 1) f24(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 ] (2, 1) f9(c, d) -> f24(c, d) [ d >= 0 /\ d >= c ] start location: f0 leaf cost: 1 By chaining the transition f0(c, d) -> f9(f, 4) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 ] with all transitions in problem 9, the following new transitions are obtained: f0(c, d) -> f24(f, 4) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ 4 >= f ] f0(c, d) -> f9(f, 5) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 ] We thus obtain the following problem: 10: T: (1, 6) f0(c, d) -> f24(f, 4) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ 4 >= f ] (1, 6) f0(c, d) -> f9(f, 5) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 ] (1, 5) f0(c, d) -> f24(f, 3) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ 3 >= f ] (1, 4) f0(c, d) -> f24(f, 2) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ 2 >= f ] (1, 3) f0(c, d) -> f24(f, 1) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ 1 >= f ] (1, 2) f0(c, d) -> f24(f, 0) [ 0 >= 0 /\ 0 >= f ] (?, 1) f9(c, d) -> f9(c, d + 1) [ d >= 0 /\ c >= d + 1 ] (?, 1) f24(c, d) -> f24(c, d) [ d >= 0 /\ -c + d >= 0 /\ 0 >= f + 1 ] (?, 1) f24(c, d) -> f24(c, d) [ d >= 0 /\ -c + d >= 0 ] (?, 1) f37(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 /\ f >= g + 1 ] (?, 1) f37(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 ] (2, 1) f24(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 ] (2, 1) f9(c, d) -> f24(c, d) [ d >= 0 /\ d >= c ] start location: f0 leaf cost: 1 By chaining the transition f0(c, d) -> f9(f, 5) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 ] with all transitions in problem 10, the following new transitions are obtained: f0(c, d) -> f24(f, 5) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ 5 >= f ] f0(c, d) -> f9(f, 6) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 ] We thus obtain the following problem: 11: T: (1, 7) f0(c, d) -> f24(f, 5) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ 5 >= f ] (1, 7) f0(c, d) -> f9(f, 6) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 ] (1, 6) f0(c, d) -> f24(f, 4) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ 4 >= f ] (1, 5) f0(c, d) -> f24(f, 3) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ 3 >= f ] (1, 4) f0(c, d) -> f24(f, 2) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ 2 >= f ] (1, 3) f0(c, d) -> f24(f, 1) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ 1 >= f ] (1, 2) f0(c, d) -> f24(f, 0) [ 0 >= 0 /\ 0 >= f ] (?, 1) f9(c, d) -> f9(c, d + 1) [ d >= 0 /\ c >= d + 1 ] (?, 1) f24(c, d) -> f24(c, d) [ d >= 0 /\ -c + d >= 0 /\ 0 >= f + 1 ] (?, 1) f24(c, d) -> f24(c, d) [ d >= 0 /\ -c + d >= 0 ] (?, 1) f37(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 /\ f >= g + 1 ] (?, 1) f37(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 ] (2, 1) f24(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 ] (2, 1) f9(c, d) -> f24(c, d) [ d >= 0 /\ d >= c ] start location: f0 leaf cost: 1 By chaining the transition f0(c, d) -> f9(f, 6) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 ] with all transitions in problem 11, the following new transitions are obtained: f0(c, d) -> f24(f, 6) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ 6 >= f ] f0(c, d) -> f9(f, 7) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 ] We thus obtain the following problem: 12: T: (1, 8) f0(c, d) -> f24(f, 6) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ 6 >= f ] (1, 8) f0(c, d) -> f9(f, 7) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 ] (1, 7) f0(c, d) -> f24(f, 5) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ 5 >= f ] (1, 6) f0(c, d) -> f24(f, 4) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ 4 >= f ] (1, 5) f0(c, d) -> f24(f, 3) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ 3 >= f ] (1, 4) f0(c, d) -> f24(f, 2) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ 2 >= f ] (1, 3) f0(c, d) -> f24(f, 1) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ 1 >= f ] (1, 2) f0(c, d) -> f24(f, 0) [ 0 >= 0 /\ 0 >= f ] (?, 1) f9(c, d) -> f9(c, d + 1) [ d >= 0 /\ c >= d + 1 ] (?, 1) f24(c, d) -> f24(c, d) [ d >= 0 /\ -c + d >= 0 /\ 0 >= f + 1 ] (?, 1) f24(c, d) -> f24(c, d) [ d >= 0 /\ -c + d >= 0 ] (?, 1) f37(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 /\ f >= g + 1 ] (?, 1) f37(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 ] (2, 1) f24(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 ] (2, 1) f9(c, d) -> f24(c, d) [ d >= 0 /\ d >= c ] start location: f0 leaf cost: 1 By chaining the transition f0(c, d) -> f9(f, 7) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 ] with all transitions in problem 12, the following new transitions are obtained: f0(c, d) -> f24(f, 7) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ 7 >= f ] f0(c, d) -> f9(f, 8) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 ] We thus obtain the following problem: 13: T: (1, 9) f0(c, d) -> f24(f, 7) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ 7 >= f ] (1, 9) f0(c, d) -> f9(f, 8) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 ] (1, 8) f0(c, d) -> f24(f, 6) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ 6 >= f ] (1, 7) f0(c, d) -> f24(f, 5) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ 5 >= f ] (1, 6) f0(c, d) -> f24(f, 4) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ 4 >= f ] (1, 5) f0(c, d) -> f24(f, 3) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ 3 >= f ] (1, 4) f0(c, d) -> f24(f, 2) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ 2 >= f ] (1, 3) f0(c, d) -> f24(f, 1) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ 1 >= f ] (1, 2) f0(c, d) -> f24(f, 0) [ 0 >= 0 /\ 0 >= f ] (?, 1) f9(c, d) -> f9(c, d + 1) [ d >= 0 /\ c >= d + 1 ] (?, 1) f24(c, d) -> f24(c, d) [ d >= 0 /\ -c + d >= 0 /\ 0 >= f + 1 ] (?, 1) f24(c, d) -> f24(c, d) [ d >= 0 /\ -c + d >= 0 ] (?, 1) f37(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 /\ f >= g + 1 ] (?, 1) f37(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 ] (2, 1) f24(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 ] (2, 1) f9(c, d) -> f24(c, d) [ d >= 0 /\ d >= c ] start location: f0 leaf cost: 1 By chaining the transition f0(c, d) -> f9(f, 8) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 ] with all transitions in problem 13, the following new transitions are obtained: f0(c, d) -> f24(f, 8) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ 8 >= f ] f0(c, d) -> f9(f, 9) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 ] We thus obtain the following problem: 14: T: (1, 10) f0(c, d) -> f24(f, 8) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ 8 >= f ] (1, 10) f0(c, d) -> f9(f, 9) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 ] (1, 9) f0(c, d) -> f24(f, 7) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ 7 >= f ] (1, 8) f0(c, d) -> f24(f, 6) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ 6 >= f ] (1, 7) f0(c, d) -> f24(f, 5) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ 5 >= f ] (1, 6) f0(c, d) -> f24(f, 4) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ 4 >= f ] (1, 5) f0(c, d) -> f24(f, 3) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ 3 >= f ] (1, 4) f0(c, d) -> f24(f, 2) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ 2 >= f ] (1, 3) f0(c, d) -> f24(f, 1) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ 1 >= f ] (1, 2) f0(c, d) -> f24(f, 0) [ 0 >= 0 /\ 0 >= f ] (?, 1) f9(c, d) -> f9(c, d + 1) [ d >= 0 /\ c >= d + 1 ] (?, 1) f24(c, d) -> f24(c, d) [ d >= 0 /\ -c + d >= 0 /\ 0 >= f + 1 ] (?, 1) f24(c, d) -> f24(c, d) [ d >= 0 /\ -c + d >= 0 ] (?, 1) f37(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 /\ f >= g + 1 ] (?, 1) f37(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 ] (2, 1) f24(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 ] (2, 1) f9(c, d) -> f24(c, d) [ d >= 0 /\ d >= c ] start location: f0 leaf cost: 1 By chaining the transition f0(c, d) -> f9(f, 9) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 ] with all transitions in problem 14, the following new transitions are obtained: f0(c, d) -> f24(f, 9) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 /\ 9 >= 0 /\ 9 >= f ] f0(c, d) -> f9(f, 10) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 /\ 9 >= 0 /\ f >= 10 ] We thus obtain the following problem: 15: T: (1, 11) f0(c, d) -> f24(f, 9) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 /\ 9 >= 0 /\ 9 >= f ] (1, 11) f0(c, d) -> f9(f, 10) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 /\ 9 >= 0 /\ f >= 10 ] (1, 10) f0(c, d) -> f24(f, 8) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ 8 >= f ] (1, 9) f0(c, d) -> f24(f, 7) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ 7 >= f ] (1, 8) f0(c, d) -> f24(f, 6) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ 6 >= f ] (1, 7) f0(c, d) -> f24(f, 5) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ 5 >= f ] (1, 6) f0(c, d) -> f24(f, 4) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ 4 >= f ] (1, 5) f0(c, d) -> f24(f, 3) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ 3 >= f ] (1, 4) f0(c, d) -> f24(f, 2) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ 2 >= f ] (1, 3) f0(c, d) -> f24(f, 1) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ 1 >= f ] (1, 2) f0(c, d) -> f24(f, 0) [ 0 >= 0 /\ 0 >= f ] (?, 1) f9(c, d) -> f9(c, d + 1) [ d >= 0 /\ c >= d + 1 ] (?, 1) f24(c, d) -> f24(c, d) [ d >= 0 /\ -c + d >= 0 /\ 0 >= f + 1 ] (?, 1) f24(c, d) -> f24(c, d) [ d >= 0 /\ -c + d >= 0 ] (?, 1) f37(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 /\ f >= g + 1 ] (?, 1) f37(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 ] (2, 1) f24(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 ] (2, 1) f9(c, d) -> f24(c, d) [ d >= 0 /\ d >= c ] start location: f0 leaf cost: 1 By chaining the transition f0(c, d) -> f9(f, 10) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 /\ 9 >= 0 /\ f >= 10 ] with all transitions in problem 15, the following new transitions are obtained: f0(c, d) -> f24(f, 10) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 /\ 9 >= 0 /\ f >= 10 /\ 10 >= 0 /\ 10 >= f ] f0(c, d) -> f9(f, 11) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 /\ 9 >= 0 /\ f >= 10 /\ 10 >= 0 /\ f >= 11 ] We thus obtain the following problem: 16: T: (1, 12) f0(c, d) -> f24(f, 10) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 /\ 9 >= 0 /\ f >= 10 /\ 10 >= 0 /\ 10 >= f ] (1, 12) f0(c, d) -> f9(f, 11) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 /\ 9 >= 0 /\ f >= 10 /\ 10 >= 0 /\ f >= 11 ] (1, 11) f0(c, d) -> f24(f, 9) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 /\ 9 >= 0 /\ 9 >= f ] (1, 10) f0(c, d) -> f24(f, 8) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ 8 >= f ] (1, 9) f0(c, d) -> f24(f, 7) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ 7 >= f ] (1, 8) f0(c, d) -> f24(f, 6) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ 6 >= f ] (1, 7) f0(c, d) -> f24(f, 5) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ 5 >= f ] (1, 6) f0(c, d) -> f24(f, 4) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ 4 >= f ] (1, 5) f0(c, d) -> f24(f, 3) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ 3 >= f ] (1, 4) f0(c, d) -> f24(f, 2) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ 2 >= f ] (1, 3) f0(c, d) -> f24(f, 1) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ 1 >= f ] (1, 2) f0(c, d) -> f24(f, 0) [ 0 >= 0 /\ 0 >= f ] (?, 1) f9(c, d) -> f9(c, d + 1) [ d >= 0 /\ c >= d + 1 ] (?, 1) f24(c, d) -> f24(c, d) [ d >= 0 /\ -c + d >= 0 /\ 0 >= f + 1 ] (?, 1) f24(c, d) -> f24(c, d) [ d >= 0 /\ -c + d >= 0 ] (?, 1) f37(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 /\ f >= g + 1 ] (?, 1) f37(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 ] (2, 1) f24(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 ] (2, 1) f9(c, d) -> f24(c, d) [ d >= 0 /\ d >= c ] start location: f0 leaf cost: 1 By chaining the transition f0(c, d) -> f9(f, 11) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 /\ 9 >= 0 /\ f >= 10 /\ 10 >= 0 /\ f >= 11 ] with all transitions in problem 16, the following new transitions are obtained: f0(c, d) -> f24(f, 11) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 /\ 9 >= 0 /\ f >= 10 /\ 10 >= 0 /\ f >= 11 /\ 11 >= 0 /\ 11 >= f ] f0(c, d) -> f9(f, 12) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 /\ 9 >= 0 /\ f >= 10 /\ 10 >= 0 /\ f >= 11 /\ 11 >= 0 /\ f >= 12 ] We thus obtain the following problem: 17: T: (1, 13) f0(c, d) -> f24(f, 11) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 /\ 9 >= 0 /\ f >= 10 /\ 10 >= 0 /\ f >= 11 /\ 11 >= 0 /\ 11 >= f ] (1, 13) f0(c, d) -> f9(f, 12) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 /\ 9 >= 0 /\ f >= 10 /\ 10 >= 0 /\ f >= 11 /\ 11 >= 0 /\ f >= 12 ] (1, 12) f0(c, d) -> f24(f, 10) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 /\ 9 >= 0 /\ f >= 10 /\ 10 >= 0 /\ 10 >= f ] (1, 11) f0(c, d) -> f24(f, 9) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 /\ 9 >= 0 /\ 9 >= f ] (1, 10) f0(c, d) -> f24(f, 8) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ 8 >= f ] (1, 9) f0(c, d) -> f24(f, 7) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ 7 >= f ] (1, 8) f0(c, d) -> f24(f, 6) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ 6 >= f ] (1, 7) f0(c, d) -> f24(f, 5) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ 5 >= f ] (1, 6) f0(c, d) -> f24(f, 4) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ 4 >= f ] (1, 5) f0(c, d) -> f24(f, 3) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ 3 >= f ] (1, 4) f0(c, d) -> f24(f, 2) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ 2 >= f ] (1, 3) f0(c, d) -> f24(f, 1) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ 1 >= f ] (1, 2) f0(c, d) -> f24(f, 0) [ 0 >= 0 /\ 0 >= f ] (?, 1) f9(c, d) -> f9(c, d + 1) [ d >= 0 /\ c >= d + 1 ] (?, 1) f24(c, d) -> f24(c, d) [ d >= 0 /\ -c + d >= 0 /\ 0 >= f + 1 ] (?, 1) f24(c, d) -> f24(c, d) [ d >= 0 /\ -c + d >= 0 ] (?, 1) f37(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 /\ f >= g + 1 ] (?, 1) f37(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 ] (2, 1) f24(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 ] (2, 1) f9(c, d) -> f24(c, d) [ d >= 0 /\ d >= c ] start location: f0 leaf cost: 1 By chaining the transition f0(c, d) -> f9(f, 12) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 /\ 9 >= 0 /\ f >= 10 /\ 10 >= 0 /\ f >= 11 /\ 11 >= 0 /\ f >= 12 ] with all transitions in problem 17, the following new transitions are obtained: f0(c, d) -> f24(f, 12) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 /\ 9 >= 0 /\ f >= 10 /\ 10 >= 0 /\ f >= 11 /\ 11 >= 0 /\ f >= 12 /\ 12 >= 0 /\ 12 >= f ] f0(c, d) -> f9(f, 13) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 /\ 9 >= 0 /\ f >= 10 /\ 10 >= 0 /\ f >= 11 /\ 11 >= 0 /\ f >= 12 /\ 12 >= 0 /\ f >= 13 ] We thus obtain the following problem: 18: T: (1, 14) f0(c, d) -> f24(f, 12) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 /\ 9 >= 0 /\ f >= 10 /\ 10 >= 0 /\ f >= 11 /\ 11 >= 0 /\ f >= 12 /\ 12 >= 0 /\ 12 >= f ] (1, 14) f0(c, d) -> f9(f, 13) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 /\ 9 >= 0 /\ f >= 10 /\ 10 >= 0 /\ f >= 11 /\ 11 >= 0 /\ f >= 12 /\ 12 >= 0 /\ f >= 13 ] (1, 13) f0(c, d) -> f24(f, 11) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 /\ 9 >= 0 /\ f >= 10 /\ 10 >= 0 /\ f >= 11 /\ 11 >= 0 /\ 11 >= f ] (1, 12) f0(c, d) -> f24(f, 10) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 /\ 9 >= 0 /\ f >= 10 /\ 10 >= 0 /\ 10 >= f ] (1, 11) f0(c, d) -> f24(f, 9) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 /\ 9 >= 0 /\ 9 >= f ] (1, 10) f0(c, d) -> f24(f, 8) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ 8 >= f ] (1, 9) f0(c, d) -> f24(f, 7) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ 7 >= f ] (1, 8) f0(c, d) -> f24(f, 6) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ 6 >= f ] (1, 7) f0(c, d) -> f24(f, 5) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ 5 >= f ] (1, 6) f0(c, d) -> f24(f, 4) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ 4 >= f ] (1, 5) f0(c, d) -> f24(f, 3) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ 3 >= f ] (1, 4) f0(c, d) -> f24(f, 2) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ 2 >= f ] (1, 3) f0(c, d) -> f24(f, 1) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ 1 >= f ] (1, 2) f0(c, d) -> f24(f, 0) [ 0 >= 0 /\ 0 >= f ] (?, 1) f9(c, d) -> f9(c, d + 1) [ d >= 0 /\ c >= d + 1 ] (?, 1) f24(c, d) -> f24(c, d) [ d >= 0 /\ -c + d >= 0 /\ 0 >= f + 1 ] (?, 1) f24(c, d) -> f24(c, d) [ d >= 0 /\ -c + d >= 0 ] (?, 1) f37(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 /\ f >= g + 1 ] (?, 1) f37(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 ] (2, 1) f24(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 ] (2, 1) f9(c, d) -> f24(c, d) [ d >= 0 /\ d >= c ] start location: f0 leaf cost: 1 By chaining the transition f0(c, d) -> f9(f, 13) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 /\ 9 >= 0 /\ f >= 10 /\ 10 >= 0 /\ f >= 11 /\ 11 >= 0 /\ f >= 12 /\ 12 >= 0 /\ f >= 13 ] with all transitions in problem 18, the following new transitions are obtained: f0(c, d) -> f24(f, 13) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 /\ 9 >= 0 /\ f >= 10 /\ 10 >= 0 /\ f >= 11 /\ 11 >= 0 /\ f >= 12 /\ 12 >= 0 /\ f >= 13 /\ 13 >= 0 /\ 13 >= f ] f0(c, d) -> f9(f, 14) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 /\ 9 >= 0 /\ f >= 10 /\ 10 >= 0 /\ f >= 11 /\ 11 >= 0 /\ f >= 12 /\ 12 >= 0 /\ f >= 13 /\ 13 >= 0 /\ f >= 14 ] We thus obtain the following problem: 19: T: (1, 15) f0(c, d) -> f24(f, 13) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 /\ 9 >= 0 /\ f >= 10 /\ 10 >= 0 /\ f >= 11 /\ 11 >= 0 /\ f >= 12 /\ 12 >= 0 /\ f >= 13 /\ 13 >= 0 /\ 13 >= f ] (1, 15) f0(c, d) -> f9(f, 14) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 /\ 9 >= 0 /\ f >= 10 /\ 10 >= 0 /\ f >= 11 /\ 11 >= 0 /\ f >= 12 /\ 12 >= 0 /\ f >= 13 /\ 13 >= 0 /\ f >= 14 ] (1, 14) f0(c, d) -> f24(f, 12) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 /\ 9 >= 0 /\ f >= 10 /\ 10 >= 0 /\ f >= 11 /\ 11 >= 0 /\ f >= 12 /\ 12 >= 0 /\ 12 >= f ] (1, 13) f0(c, d) -> f24(f, 11) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 /\ 9 >= 0 /\ f >= 10 /\ 10 >= 0 /\ f >= 11 /\ 11 >= 0 /\ 11 >= f ] (1, 12) f0(c, d) -> f24(f, 10) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 /\ 9 >= 0 /\ f >= 10 /\ 10 >= 0 /\ 10 >= f ] (1, 11) f0(c, d) -> f24(f, 9) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 /\ 9 >= 0 /\ 9 >= f ] (1, 10) f0(c, d) -> f24(f, 8) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ 8 >= f ] (1, 9) f0(c, d) -> f24(f, 7) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ 7 >= f ] (1, 8) f0(c, d) -> f24(f, 6) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ 6 >= f ] (1, 7) f0(c, d) -> f24(f, 5) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ 5 >= f ] (1, 6) f0(c, d) -> f24(f, 4) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ 4 >= f ] (1, 5) f0(c, d) -> f24(f, 3) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ 3 >= f ] (1, 4) f0(c, d) -> f24(f, 2) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ 2 >= f ] (1, 3) f0(c, d) -> f24(f, 1) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ 1 >= f ] (1, 2) f0(c, d) -> f24(f, 0) [ 0 >= 0 /\ 0 >= f ] (?, 1) f9(c, d) -> f9(c, d + 1) [ d >= 0 /\ c >= d + 1 ] (?, 1) f24(c, d) -> f24(c, d) [ d >= 0 /\ -c + d >= 0 /\ 0 >= f + 1 ] (?, 1) f24(c, d) -> f24(c, d) [ d >= 0 /\ -c + d >= 0 ] (?, 1) f37(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 /\ f >= g + 1 ] (?, 1) f37(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 ] (2, 1) f24(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 ] (2, 1) f9(c, d) -> f24(c, d) [ d >= 0 /\ d >= c ] start location: f0 leaf cost: 1 By chaining the transition f0(c, d) -> f9(f, 14) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 /\ 9 >= 0 /\ f >= 10 /\ 10 >= 0 /\ f >= 11 /\ 11 >= 0 /\ f >= 12 /\ 12 >= 0 /\ f >= 13 /\ 13 >= 0 /\ f >= 14 ] with all transitions in problem 19, the following new transitions are obtained: f0(c, d) -> f24(f, 14) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 /\ 9 >= 0 /\ f >= 10 /\ 10 >= 0 /\ f >= 11 /\ 11 >= 0 /\ f >= 12 /\ 12 >= 0 /\ f >= 13 /\ 13 >= 0 /\ f >= 14 /\ 14 >= 0 /\ 14 >= f ] f0(c, d) -> f9(f, 15) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 /\ 9 >= 0 /\ f >= 10 /\ 10 >= 0 /\ f >= 11 /\ 11 >= 0 /\ f >= 12 /\ 12 >= 0 /\ f >= 13 /\ 13 >= 0 /\ f >= 14 /\ 14 >= 0 /\ f >= 15 ] We thus obtain the following problem: 20: T: (1, 16) f0(c, d) -> f24(f, 14) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 /\ 9 >= 0 /\ f >= 10 /\ 10 >= 0 /\ f >= 11 /\ 11 >= 0 /\ f >= 12 /\ 12 >= 0 /\ f >= 13 /\ 13 >= 0 /\ f >= 14 /\ 14 >= 0 /\ 14 >= f ] (1, 16) f0(c, d) -> f9(f, 15) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 /\ 9 >= 0 /\ f >= 10 /\ 10 >= 0 /\ f >= 11 /\ 11 >= 0 /\ f >= 12 /\ 12 >= 0 /\ f >= 13 /\ 13 >= 0 /\ f >= 14 /\ 14 >= 0 /\ f >= 15 ] (1, 15) f0(c, d) -> f24(f, 13) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 /\ 9 >= 0 /\ f >= 10 /\ 10 >= 0 /\ f >= 11 /\ 11 >= 0 /\ f >= 12 /\ 12 >= 0 /\ f >= 13 /\ 13 >= 0 /\ 13 >= f ] (1, 14) f0(c, d) -> f24(f, 12) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 /\ 9 >= 0 /\ f >= 10 /\ 10 >= 0 /\ f >= 11 /\ 11 >= 0 /\ f >= 12 /\ 12 >= 0 /\ 12 >= f ] (1, 13) f0(c, d) -> f24(f, 11) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 /\ 9 >= 0 /\ f >= 10 /\ 10 >= 0 /\ f >= 11 /\ 11 >= 0 /\ 11 >= f ] (1, 12) f0(c, d) -> f24(f, 10) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 /\ 9 >= 0 /\ f >= 10 /\ 10 >= 0 /\ 10 >= f ] (1, 11) f0(c, d) -> f24(f, 9) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ f >= 9 /\ 9 >= 0 /\ 9 >= f ] (1, 10) f0(c, d) -> f24(f, 8) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ f >= 8 /\ 8 >= 0 /\ 8 >= f ] (1, 9) f0(c, d) -> f24(f, 7) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ f >= 7 /\ 7 >= 0 /\ 7 >= f ] (1, 8) f0(c, d) -> f24(f, 6) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ f >= 6 /\ 6 >= 0 /\ 6 >= f ] (1, 7) f0(c, d) -> f24(f, 5) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ f >= 5 /\ 5 >= 0 /\ 5 >= f ] (1, 6) f0(c, d) -> f24(f, 4) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ f >= 4 /\ 4 >= 0 /\ 4 >= f ] (1, 5) f0(c, d) -> f24(f, 3) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ f >= 3 /\ 3 >= 0 /\ 3 >= f ] (1, 4) f0(c, d) -> f24(f, 2) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ f >= 2 /\ 2 >= 0 /\ 2 >= f ] (1, 3) f0(c, d) -> f24(f, 1) [ 0 >= 0 /\ f >= 1 /\ 1 >= 0 /\ 1 >= f ] (1, 2) f0(c, d) -> f24(f, 0) [ 0 >= 0 /\ 0 >= f ] (?, 1) f9(c, d) -> f9(c, d + 1) [ d >= 0 /\ c >= d + 1 ] (?, 1) f24(c, d) -> f24(c, d) [ d >= 0 /\ -c + d >= 0 /\ 0 >= f + 1 ] (?, 1) f24(c, d) -> f24(c, d) [ d >= 0 /\ -c + d >= 0 ] (?, 1) f37(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 /\ f >= g + 1 ] (?, 1) f37(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 ] (2, 1) f24(c, d) -> f37(c, d) [ d >= 0 /\ -c + d >= 0 ] (2, 1) f9(c, d) -> f24(c, d) [ d >= 0 /\ d >= c ] start location: f0 leaf cost: 1 Complexity upper bound ? Time: 2.818 sec (SMT: 2.579 sec)